Masculinity in Older Black Men: Implications for Adult Education - Manuel Solomon; Lorenzo Bowman (Adult Education Research Conference, 2018)
This paper examines the manifestation of masculinity among older Black men in the United States. The findings from a content analysis conducted on the covers of three popular magazines reveal that Black men embrace an alternative or complicit form of masculinity. This alternative or complicit form of masculinity can be an impediment to teaching and learning for Black men.
Keywords: masculinity; hegemonic masculinity; Black men